2017
DOI: 10.1039/c6md00466k
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-based variation as a biomarker of sensitivity to molecularly targeted therapy in melanoma

Abstract: Transcriptomic phenotypes defined for melanoma have been reported to correlate with sensitivity to various drugs. In this study, we aimed to define a minimal signature that could be used to distinguish melanoma sub-types in vitro, and to determine suitable drugs by which these sub-types can be targeted. By using primary melanoma cell lines, as well as commercially available melanoma cell lines, we find that the evaluation of MLANA and INHBA expression is as capable as one based on a combined analysis performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…In line with our earlier findings 27 , we show here for the first time in vitro, that Lapatinib and Midostaurin are candidates for such combination therapy, as they target selectively either NS/E or CS/M cells, respectively. Even though EMT might be a signature shared among tumor types, combination treatment suggestions obtained for breast cancer in this study are different from those we found for other tumor types, such as colon cancer and melanoma 68,69 . One explanation for this can be that NS/E and CS/M cell types defined for tumors originating from different tissues actually define different phenotypes in the EMT or plasticity scale.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our earlier findings 27 , we show here for the first time in vitro, that Lapatinib and Midostaurin are candidates for such combination therapy, as they target selectively either NS/E or CS/M cells, respectively. Even though EMT might be a signature shared among tumor types, combination treatment suggestions obtained for breast cancer in this study are different from those we found for other tumor types, such as colon cancer and melanoma 68,69 . One explanation for this can be that NS/E and CS/M cell types defined for tumors originating from different tissues actually define different phenotypes in the EMT or plasticity scale.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, resistant subgroups showed significant enrichments of gene sets related to epithelial-mesenchymal transition and multicancer invasiveness signatures, indicating an invasive/mesenchymal phenotype in resistant cells (Figure B). These results are concordant with previous findings where melanoma cells were classified into invasive, proliferative, and intermediate categories …”
supporting
confidence: 93%
“…These results are concordant with previous findings where melanoma cells were classified into invasive, proliferative, and intermediate categories. 14 To further investigate mechanisms behind resistance to 10a, we performed protein−chemical interaction network analysis with 46 genes using the NetworkAnalyst 16 online tool. This revealed that, out of 18 resistance associated proteins, 15 extensively interact with a pyrazolopyrimidine derivative and three histone deacetylase (HDAC) inhibitors, valproic acid, trichostatin A, and entinostat (Figure 3).…”
mentioning
confidence: 99%
“…The rationale for targeting HSP90 is supported not only by a high level of this protein in cancer cells, but also by cancer cellselective formation of HSP90 multi-chaperone complexes exerting a high ATPase activity [74]. In addition, HSP90 has been identified as a crucial regulator of melanoma cell phenotype, and inhibition of HSP90 has substantially affected both commercially available and primary melanoma cell lines [75], also those resistant to currently available therapeutics [76]. A number of natural and synthetic compounds of different chemical structures and binding sites have been identified as selective HSP90 inhibitors (Fig.…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%